Toponimi dan Julukan dalam Place Branding Kabupaten Garut - Wahyuningtyas, Laras Annisa; Priyatna, Centurion Chandratama; Erwina, Wina (Balai Bahasa Sulawesi Selatan, 2025)
This study analyzes the place branding strategy of Garut Regency, focusing on toponymy dynamics, historical nicknames, and the role of Penta-helix collaboration in addressing identity fragmentation and brand credibility gaps. Using a qualitative interpretive case study design, the research explores how stakeholders negotiate meanings within complex social contexts. Data were collected through in-depth interviews with 14 key informants representing Government, Academia, Business, Community, and Media, supported by documentation studies. Analysis followed Miles and Huberman’s interactive model. The findings show that multiple nicknames such as “Kota Intan,” “Swiss van Java,” and “Joyful Garut” create contrasting perceptions, with some viewing them as cultural richness and others as confusing identity signals. A notable credibility gap also emerges between brand promises and on-the-ground realities. Penta-helix synergy remains limited due to top-down initiatives that lack grounding in local values. The study recommends positively reinterpreting toponymy and strengthening an integrated, collaborative governance ecosystem. AbstrakPenelitian ini menganalisis strategi place branding Kabupaten Garut dengan menyoroti dinamika toponimi, julukan historis, serta peran kolaborasi Penta-helix dalam mengatasi fragmentasi identitas dan kesenjangan kredibilitas merek. Menggunakan pendekatan kualitatif studi kasus interpretif, data dikumpulkan melalui wawancara mendalam dengan 14 informan dari unsur Pemerintah, Akademisi, Bisnis, Komunitas, dan Media, serta studi dokumentasi. Analisis mengikuti model interaktif Miles dan Huberman. Hasil penelitian menunjukkan bahwa beragam julukan seperti “Kota Intan,” “Swiss van Java,” dan “Joyful Garut” memunculkan makna yang dipersepsikan berbeda, sebagian dianggap sebagai kekayaan budaya, namun juga memicu kebingungan identitas. Kesenjangan antara janji merek dan kondisi faktual turut memperlemah kredibilitas. Kolaborasi Penta-helix belum optimal karena inisiatif cenderung top-down dan kurang berbasis nilai lokal. Studi ini merekomendasikan reinterpretasi positif toponimi serta penguatan tata kelola kolaboratif yang lebih terpadu.